From lifeguard to bitch: The problem of promiscuous categories in story telling via video chat by a long-distance couple - Fitzgerald, Richard; Rintel, Sean (Australian Journal of Communication, 2013)
This paper examines a single case of story telling between a couple in a long-distance relationship conducted via video calling. Drawing on Membership Categorisation Analysis (MCA) we examine the way the teller incrementally reveals information about a character in order to build a story of coincidences. In doing this, however, the recipient begins to treat the evolving character as relevant to a different device, that of their relationship. Our discussion develops on the analysis of omnirelevance devices (Sacks, 1995) by examining how categories can be shifted between devices. In so doing, we highlight the way categories introduced for one task may be put to other uses; that is, how categories may become ‘promiscuous’.
Fitzgerald, R. & Rintel, S. (2013). From lifeguard to bitch: The problem of promiscuous categories in story telling via video chat by a long-distance couple. Australian Journal of Communication, 40 (2). Online version is free and includes video (use Publisher URL)